Left ventricular torsional mechanics in term fetuses and neonates. (8th January 2020) - Patey, O.; Carvalho, J. S.; Thilaganathan, B.
ABSTRACT: Objective: Left ventricular (LV) torsion is an important aspect of cardiac mechanics and is fundamental to normal ventricular function. The myocardial mechanics of the fetal heart and the changes that occur during the transition to the neonatal period have not been explored previously. The aim of this study was to evaluate perinatal changes in LV torsion and its relationship with myocardial function. Methods: This was a prospective study of 36 women with an uncomplicated term pregnancy. Fetal and neonatal conventional, spectral tissue Doppler and two‐dimensional (2D) speckle tracking echocardiography were performed a few days before and within hours after delivery to measure cardiac indices including LV rotational parameters derived from short‐axis views at the base and apex of the heart. Linear regression analysis was used to examine the relationship between LV rotational parameters and cardiac geometric and functional indices in term fetuses and neonates. Perinatal changes in LV rotational parameters were assessed. Results: There were three patterns of LV twist in term fetuses: those with reversed‐apex‐type LV twist had the lowest median values of LV torsion (0.1°/cm), with higher values (1.6°/cm) in those with infant‐type LV twist and the highest values (4.4°/cm) in those with adult‐type LV twist. LV torsion was associated significantly with cardiac geometric and functional indices. Perinatal evaluation revealed a significant increase in LV torsion following delivery in fetuses exhibiting reversed‐apex‐type LV twist (increase of 2.8°/cm, P = 0.009) and a significant decrease in those with adult‐type LV twist (decrease of 3.2°/cm, P = 0.008). Conclusions: This study demonstrates the feasibility of 2D speckle tracking imaging for accurate assessment of rotational cardiac parameters in term fetuses. There are unique perinatal patterns of LV twist that demonstrate different values of LV torsion, which was found to correlate with indices of ventricular geometry and myocardial function. Differences in patterns of LV twist may therefore reflect differences in compensatory myocardial adaptation to the physiological environment/loading conditions in late gestation in fetuses and postnatal cardiac adjustment to the acute loading changes that occur at delivery. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.